Roles of global and regional networks and consortia in strengthening forestry research - Nair, C.T.S.; Dykstra, D.P. (1998)
Collaborative institutional arrangements such as networks and consortia are becoming significant players in the provision of goods and services in situations where such collaborations can improve the overall comparative advantage of the alliance. Economic globalisation, rapid development of communication technologies, and increasing problem complexity have enhanced the relevance of networks and other such arrangements. While networks and strategic alliances are an integral part of business and industry, and are playing an increasingly important role in national and international agriculture research (APAARI 1997) they have been less widely used in forestry for collaborative research. Convinced that both the efficiency and effectiveness of forestry research could be improved through strategic alliances, the Fourth Session of the Intergovernmental Panel on Forests stressed the need to "promote consortia and networks to lead and organize research" (IISD 1997). Historically, forestry among research networks have been created principally to foster the exchange of information among scientists and to a lesser extent, users and beneficiaries of forestry research. This was the primary aim of IUFRO, by far the largest and oldest forestry research network, when it was created in 1892. For nearly all forestry research network, including IUFRO, exchange of information continues to be a primary focus but recent developments in foresty suggest that by broadening the scope of their activities, these networks could potentially contribute much more to forestry research. Numerous research problems can potentially be handled more effectively through networking than by individual research institutes. National research systems are often constrained by lack of expertise and resources, and networks can help overcome these limitations. Making this potential a reality requires a clear understanding of the role of networks and consortia, as well as their potential strengths and limitations. In this paper we examine a selection of issues relating to collaboration in forestry research through networks and consortia at the regional and global levels. We make no pretence that our treatment provides a comprehensive overview of this subject. Rather than attempting to catalogue the many forestry research networks and collaborative arrangem ents that exist, our objective is to raise issues that might be fruitfully discussed during the ICRIS dialogue